Video transcoding from H.264/AVC to MPEG-2 with reduced computational complexity - Moiron, Sandro (2009)
This paper addresses video transcoding from H.264/AVC into MPEG-2 with reduced complexity and high rate-distortion efficiency. While the overall concept is based on a cascaded decoder-encoder, the novel adaptation methods developed in this work have the advantage of providing very good performance in H.264/AVC to MPEG-2 transcoding. The proposed approach exploits the similarities between the coding tools used in both standards, with the objective of obtaining a computationally efficient transcoder without penalising the signal quality. Fast and efficient methods are devised for conversion of macroblock coding modes and translation of motion information in order to compute the MPEG-2 coding format with a reduced number of operations, by reusing the corresponding data embedded in the incoming H.264/AVC coded stream. In comparison with a cascaded decoder-encoder, the fast transcoder achieves computational complexity savings up to 60% with slightly better peak signal-to-noise ratio (PSNR) at the same bitrate.